Molecular design and characterization of recombinant long half-life mutants of human tissue factor pathway inhibitor - Bai, Hao; Ma, Duan; Zhang, Yu-Gao; Zhang, Nong; Kong, De-Sheng; Guo, Hong-Shen; Mo, Wei; Tang, Qi-Qun; Song, Hou-Yan (Thrombosis and Haemostasis, 2005)
Tissue factor pathway inhibitor (TFPI) is a physiological inhibitor of extrinsic pathway of coagulation and has biological functions of anticoagulation and anti-inflammation. Although TFPI has been proved to be a good therapeutic agent of sepsis, inflammatory shock, and DIC, the clinical application and therapeutic effects of TFPI are impeded because of its short half-life in vivo. In order to prolong the half-life of TFPI, homology modeling and molecule docking were performed on a computer workstation principally in protein structural biology and binding characteristics between TFPI and its receptor LRP (low-density lipoprotein receptor related protein). Two recombinant long half-life human TFPI mutants coined TFPI-Mut1 and TFPI-Mut4 were designed and expressed in E.coli. In comparison with the wild-type TFPI, TFPI-Mut1 and TFPI-Mut4 presented a few of changes in spatial configuration and a decrease in relative Gibbs free energy of docking complex by 17.3% and 21.5%, respectively, as indicated by a computer simulation. After refolding and purification, anticoagulant activities, anti-TF/FVIIa and anti-FXa activities of the mutants were found to be the same as those of wide-type TFPI. The pharmacokinetics research indicated that alpha phase half-life (t1/2α) of TFPI-Mut1 and TFPI-Mut4 were prolonged 1.33-fold and 1.96-fold respectively, beta phase half-life (t1/2 β) of TFPI-Mut1 and TFPI-Mut4 were prolonged 1.62-fold and 4.22-fold respectively. These results suggested that TFPI-Mut1 and TFPI-Mut4 maintained the bioactivities of wild-type TFPI, prolonged half-life in vivo simultaneously and were expected for better clinical value and therapeutic effect.
Keywords: TFPI; half-life; mutants; pharmacokinetics